Acetaldehyde reactions during wine bottle storage. (30th August 2019) - Han, Guomin; Webb, Michael R.; Waterhouse, Andrew L.
Highlights: Microoxygenation of wine yields differential levels of acetaldehyde. Acetaldehyde alters wine composition. The changes mimic aging. Managing microoxygenation can alter the trajectory of wine aging. Abstract: Acetaldehyde is a major wine oxidation product. Here, three Cabernet Sauvignon wines, containing different levels of acetaldehyde from different micro-oxygenation (mOx) regimes, including yeast-mediated treatments, were aged under closures differing in oxygen ingress. Oxygen, phenolics, carbonyls and heterocyclic acetals were measured. Acetaldehyde levels at bottling was a significant factor in the phenolic compound profile after one year, with anthocyanins most affected, then flavonols, flavonoids and hydroxycinnamic acids, but there were negligible effects on benzoic acids. The effect of bottle closures with increased oxygen ingress had a similar trend. Increased acetaldehyde levels and oxygen ingress also yielded higher levels of the heterocyclic acetals from glycerol. These changes reflect aging, and suggest that managing mOx during production could be used to reduce the time needed to achieve some aged wine characteristics.